Pengaruh Dana Alokasi Umum Dan Dana Alokasi Khusus Terhadap Indeks Pembangunan Manusia Pada Kab/ Kota Propinsi Sumatera Utara - Riva Ubar Harahap (KITABAH: Jurnal Akuntansi dan Keuangan Syariah, 2018)
The purpose of this study is to test and analyze the influence of special allocation fund, and general allocation fund both simultaneously and partially on the human development index. This study uses secondary data in the form of panel data (pooled data) from 33 districts / cities. The data analysis model used to test the hypothesis in this study is multiple linear regression (Multiple Regression Analysis). The results of statistical testing can be concluded that general allocation fund and special allocation fund affect human development index (HDI) simultaneously. Likewise, the test results prove that general allocation fund partially affects the human development index (HDI). The results of the special allocation fund testing also partially influence the human development index (HDI). This study does not separate the allocation of special allocation fund in fields such as education, health, roads, irrigation, clean water, maritime affairs and fisheries and agriculture. In addition, the allocation of special allocation fund per sector in each region varies depending on the national development priorities determined by the central government and the Regional Government.